Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE Bath, Basin, and Bedroom Ware can be kept clean with soap and water. If a “tide-mark” appears on the bath, the use of a cleansing powder on a damp cloth is effective. The chamber should be cleaned daily with boiling water and soda. China and Glass can be made to look beautifully bright if washed in soapy water. When washing delicate articles, place a cloth in the bottom of the bowl to prevent chipping and scratching. Silver and Plated Articles can be kept clean and bright if they are washed in hot soapy water. They should be rinsed in hot water, dried quickly, and then rubbed with a leather. To Wash Dishes. — First, put forks, spoons, and knives in one heap; crockery that is not greasy in one pile, and greasy dishes by themselves. Use clean, hot water, and plenty of it. Make a soapy lather, using a soap-saver, which can be bought very cheaply or easily made (see p. 13). A washing-up mop can be bought for a few pence, and it is not necessary to put the hands into very hot water. Wash glassware first; then forks, etc.; then tea-cups and plates; last of all greasy dishes. Crockery washed in this way does not soil the tea-cloths, the dish-cloth does not get clogged with grease, and the dishes shine as if new. Saucepans, frying-pans, etc., are best cleaned at once, when hot, first using a piece of tissue paper to remove the greater part of the grease ; they can be done in half the time if not allowed to get cold and greasy. Greasy iron saucepans should be partly filled with hot water, a piece of soda added, and the pan put on to boil before washing. Saucepans used for food of a floury nature should be filled with cold water and Page Twelve 177/5/8/1